Aplicación de medidas sustitutivas por incumplimiento en el pago de pensiones alimenticias, para evitar se vulneren los derechos de las niñas, niños y adolescentes - Carreño Castillo, Natali Carlota (2018)
Alimony is a right that is established for the benefit of children and adolescents in order to cover their basic needs as food, clothing, education, health, among other essentials for daily subsistence. Either so the payment of this alimony is mandatory voluntarily or when the respective demand is made so that by judicial order it is obliged to pay the obligor the fulfillment of this duty according to the income of the defendant. A problem has been identified at the national level, such as the failure to pay alimony that violates the rights of girls, boys and adolescents, which by means of this investigation it will be demonstrated that for the benefit of the fed and the obliging one it would be the prison in the days of rest for the obligor by default in alimony that it will be applied as a substitute measure in case the obligor stops depositing the pension or if the fed suffers some circumstance of life that cannot be foreseen, such as losing their job to have the possibility of looking for a job that allows them to generate income to fulfill their obligation and thus not being affected or violated the rights of the fed as it would have an income to cover their daily basic needs without interrupting their development integral……….